Versatile Synthesis of Trisphosphines Bearing Phenylene and Vinylene Backbones Useful for Metal Catalysis and Materials Applications - Doba, Takahiro; Fukuma, Shota; Shang, Rui; Nakamura, Eiichi (Synthesis, 2022)
Trisphosphines, in which two phenylene or vinylene backbones connect three phosphine atoms, belong to an emerging class of ligands in metal-catalyzed organic synthesis and materials applications. However, these ligands were previously known only in a small variety because of the synthetic limitations. We report herein two versatile synthetic routes to a hitherto unavailable variety of trisphosphines. The compounds bearing phenylene backbones were synthesized by sequential addition of two different organolithium reagents to triphenyl phosphite and that with vinylene backbones by stereoretentive addition of lithium diarylphosphide to a cis-bromoalkene. The new trisphosphine compounds will serve as valuable tools for the development of transition-metal-catalyzed reactions and functional materials.
Keywords: phosphine ligand; tridentate; organolithium; phenylene backbone; vinylene backbone; materials